1993
DOI: 10.2514/3.11365
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of a three-dimensional bluff-body wake

Abstract: The flowfield behind the wavy-cylinder geometry has been examined using flow visualization, total pressure surveys, and two-component laser Doppler anemometry. The topology of the boundary-layer separation line is linked to the subsequent three-dimensional development of the mean and turbulent structures of the wake. The formation of trailing streamwise vortices behind the nodal points of separation results in a locally narrower wake, a more rapid wake velocity recovery, and suppression of the turbulence devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(16 citation statements)
references
References 8 publications
2
14
0
Order By: Relevance
“…In the recent few years, several types of cylinders with surface profile varying sinusoidally along their spanwise direction, named wavy cylinders, were introduced (see figure 1). Ahmed & Bays-Muchmore (1992), Ahmed, Khan & Bays-Muchmore (1993), Tombazis & Bearman (1997), Bearman & Owen (1998), Owen, Szewczyk & Bearman (2000), Darekar & Sherwin (2001a, b), Keser et al (2001), Lam et al (2004), Lam, Wang & So (2004), Zhang, Dai & Lee (2005), Dobre, Hangan & Vickery (2006), Lee & Nguyen (2007) and Lam & Lin (2007, 2008 have investigated various types of wavy objects experimentally and numerically under different flow conditions. Their studies are summarized in table 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent few years, several types of cylinders with surface profile varying sinusoidally along their spanwise direction, named wavy cylinders, were introduced (see figure 1). Ahmed & Bays-Muchmore (1992), Ahmed, Khan & Bays-Muchmore (1993), Tombazis & Bearman (1997), Bearman & Owen (1998), Owen, Szewczyk & Bearman (2000), Darekar & Sherwin (2001a, b), Keser et al (2001), Lam et al (2004), Lam, Wang & So (2004), Zhang, Dai & Lee (2005), Dobre, Hangan & Vickery (2006), Lee & Nguyen (2007) and Lam & Lin (2007, 2008 have investigated various types of wavy objects experimentally and numerically under different flow conditions. Their studies are summarized in table 1.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the separated flow structures near the geometric nodes are distinctly asymmetric for a large fraction of time, and the sectional drag coefficients at the geometric nodes are greater than that at the geometric saddle. Ahmed et al (1993) further investigated experimentally the turbulent wake behind a wavy cylinder. They described the topology of the boundary layer separation lines and the subsequent three-dimensional development of turbulent structure of the wake.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmed & Bays-Muchmore (1992) and Ahmed, Khan & Bays-Muchmore (1993) investigated experimentally the pressure field and flow patterns over a wavy cylinder. Lam et al (2004a) and Lam, Wang & So (2004b) performed experiments to deal with the drag reduction and the relevant flow-induced vibration for different wavy cylinders.…”
Section: Introductionmentioning
confidence: 99%
“…The wavy trailing edge used by Tombazis and Bearman 10 caused vortex splitting in the wake due to the phase mismatch between two neighboring cells of different shedding frequencies. In the work with wavy circular cylinders, 8,9,12,13 the three-dimensionality was caused by differences in the flow characteristics between the nodal and saddle planes. Lam et al 12 observed that the wake in the formation region of the saddle plane was wider than that of the nodal plane.…”
Section: B Spanwise Forcingmentioning
confidence: 99%
“…Some researchers [7][8][9][10][11][12][13][14] created a geometric boundary condition that varied in the spanwise direction, with the goal of influencing the global wake dynamics. Park et al 7 concluded that variation of the wake width in the spanwise direction forced the Kármán vortex street to lose its twodimensional nature and thus led to vortex dislocations and reduced drag.…”
Section: B Spanwise Forcingmentioning
confidence: 99%